Species-Level Analysis of Human Gut Microbiota With Metataxonomics - Yang, Jing; Pu, Ji; Lu, Shan; Bai, Xiangning; Wu, Yangfeng; Jin, Dong; Cheng, Yanpeng; Zhang, Gui; Zhu, Wentao; Luo, Xuelian; Rosselló-Móra, Ramon; Xu, Jianguo (Frontiers in Microbiology, 2020)
Our current understanding of the gut microbial community in humans is mainly limited to taxonomic features at the genus level, which so far has generated erroneous information. Here, we examined the gut microbial community in humans at the species-level by metataxonomics. To achieve this, we used a high-throughput approach involving operational phylogenetic unit analysis of the almost full-length 16S rRNA gene sequence. A total of 1,235 species-level phylotypes (SLPs) were classified from the feces of 120 healthy individuals from China, including 461 classified species, 358 potentially new species and 416 potentially new taxa, which were grouped into transient, accompanying and resident bacteria categories based on their prevalence. Each individual harbored on average 186 ± 51 SLPs. There was no universal bacterial species shared by all individuals. However, all individuals shared part of a universal species pool, defined as the resident bacteria group, which included 116 SLPs. Thirty-two of 38 resident species can be found in at least one of other culture-dependent or -independent human gut microbiota research, and there were six species exclusively present in this study. Using compositional approach analysis, a hierarchical clustering of the prevalence and relative abundance of the 1,235 SLPs revealed two types of gut microbial communities, which were dominated by Prevotella copri and Bacteroides vulgatus. The type dominated by P. copri was more prevalent in northern China, while B. vulgatus dominant type was more prevalent in southern China. Therefore south-type and north-type gut microbial community in China was proposed. It was found that 166 out of 461 known bacterial species had been previously reported as pathobionts, and individuals harbored on average 20 pathobionts. The most abundant pathobionts were Klebsiella pneumoniae and Bacteroides fragilis.